(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
This study seeks to identify the role that individual financial decisions play in influencing individuals and their impact on achieving well-being and financial stability for the lives of individuals through analyzing some opinions of customers of some private banks in Baghdad, where a survey list was used as a main tool for collecting primary data, as it was subjected to this analysis. 165 customers and a number of investors in the stock market who have a current bank account, where the sample was distributed (50) consumers and (37) investors and (59) savers and (11) hoarders and relied on the statistical program (spss). The study resulted in important results about the need for private bank customers to show interest in individual financial decisions, because of its importance in managing the lives and well-being of individuals. Presenting offers to customers.